Developmental constraints in the repeated evolution of male tail characters in rhabditid and diplogastrid nematodes - Karin Kiontke; Simone Kolysh; Rocio Ng; David H. A. Fitch (PLoS ONE, 2026)
A longstanding question in evolutionary biology is how change might be restricted or biased due to developmental constraints. To address this question, we investigated three recurrently evolving characters in rhabditid nematode male tails: tail tip morphogenesis, the number of genital papillae (GPs or “rays”), and phasmid position relative to the three most posterior GPs. This new analysis incorporates taxa (rhabditids Cruznema tripartitum , Haematozoon subulatum , Poikilolaimus oxycercus , diplogastrid Diplogasteroides nasuensis , and outgroup representative Brevibucca saprophaga ) representing more and deeper divergence points in the rhabditid phylogeny than in previous analyses, allowing better resolution of ancestral states and changes. Analysis of GP characters was accomplished via immunofluorescent staining of adherens junctions at different stages of GP development and laser microbeam ablations of GP primordia. Findings include the following: (1) Loss and gain of tail tip morphogenesis occurred multiple times, possibly involving differences in fusion. (2) The pattern of GP anlagen in early L4 males is highly conserved and compatible with the previously proposed “archetype,” but is established at different developmental times in different species, consistent with constraint on GP patterning by the cell lineage and anteroposterior and dorsoventral patterning systems. (3) The stem species of Rhabditina likely had 8 GPs, with the second GP (v2) gained after the divergence of Poikilolaimus ; within rhabditids, a different GP (v6) appears to be lost twice independently. (4) Laser ablation showed that changes in phasmid position relative to GPs are not due to changes in cell lineage, but instead due to migratory switches in the relative positions of precursors of phasmid socket cells and GPs; these cell migrations occur at different developmental times in different species. In summary, our results indicate a strong constraint imposed on the cell lineage and dorsoventral positioning of GP precursors, with GP pattern diversity allowed by cell-specific migratory behavior.